Monitoring Leaching Fraction for Irrigation Scheduling in Container Nurseries - Jeff Million; Tom Yeager (EDIS)
Scheduling irrigation in container nurseries can be a daunting task for producers. There is a great risk of under- or over-watering. The leaching fraction (LF) test is a valuable tool for measuring the volume of container drainage collected during irrigation relative to the volume of water entering the container. With this test, producers can adjust their irrigation to maintain a low percentage of leaching. This 4-page fact sheet explains how to perform the test, gives example calculations, and provides some suggestions on how to utilize LF testing when managing irrigation. Written by Jeff Million and Tom Yeager, and published by the Environmental Horticulture Department, December 2015.